PENGARUH EKSTRAK AIR DAUN SEMBUKAN (Paederia foetida LINN.) TERHADAP MORFOMETRI DAN KELULUSHIDUPAN FETUS MENCIT (Mus musculus L.) - Dyah Noprianti; Sudiastuti Sudiastuti; Rudy Agung Nugroho (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2018)
Paederia foetida Linn, known locally in East Kalimantan as Sembukan, is one of the plants that is used as raw materials of traditional medicine in Indonesia. The sembukan contains a variety of chemical compounds that can affect on the development of the mice fetus. Current research aimed to evaluate the effects of boiled-water extract of Sembukan leaves on the weight and length of fetus, the total number of fetus, and fetus survival. In total of 12 pregnant mouse were randomly divided into three groups, namely control (K) without treatment, P1 treated by 175 mg/kgbb extract, and P2 treated by 350 mg/kgbb extract. After 18 days of pregnancy, mouse were sacrificed to evaluate the morphometry and survival of the fetus. The results showed that Sembukan leaves extract caused a significant (P<0.05) different on the fetus weight, amount of fetus and the number of life fetus between control (K) and treatment groups (P1 and P2). However, the treatment of any doses (P1 and P2) of Sembukan leaves extract did not show significantly differences (P>0.05) on the fetus length and the number of dead fetuses. This finding concluded that Sembukan leaves is beneficial to increase the weight and the number of live fetus of mice.